Obstructive Sleep Apnea Epidemiology, Pathomechanism and Treatment - Bikov, Andras; Dragonieri, Silvano (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Obstructive sleep apnea (OSA) is a common disease that may affect up to 50% of the adult population and whose incidence, as well as its health and socio-economic burden, continues to rise. OSA is a well-known risk factor for motor vehicle accidents and decreased work performance, and it is frequently accompanied by cardiovascular diseases. The aim of this Special Issue is to focus on the characteristics of OSA in special populations that are less frequently investigated. For this purpose, seven groups of experts in the field of sleep medicine contributed noteworthy manuscripts on this subject. The content of these articles, which include the latest knowledge about the epidemiology, pathophysiology and comorbidities of OSA in special populations, will support all physicians who endeavor to improve their understanding of this disease and can serve as a basis for future research.